Efforts to Improve Understanding of Zakat Fitrah Provisions by Using the Problem-Solving Method in the Fiqh Subject for Class V at MI Al-Huda Karang Melati Oku Timur - Ahmad Munaji (Sekolah Tinggi Ilmu Ekonomi Syariah Nahdlatul Ulama Bengkulu, 2024)
Background: The purpose of this study is to describe the improvement of learning achievement through the Problem Solving learning model in Fiqh learning for fifth grade students of MI AL-Huda. Method: The method used in this study is the Classroom Action Research (CAR) method. This method is carried out in four stages, namely planning, action, observation, and reflection. The four stages are in one cycle that is carried out repeatedly with the same steps and remains focused on how to solve problems (answers) by finding it yourself, investigating yourself and searching for information using the Problem Solving learning model. Results: From the results obtained by researchers, students' fiqh learning outcomes have increased by using audio-visual media. This is evidenced by the percentage of learning outcomes in stage 1 50%, stage 2 88% and stage 3 99%. Conclusion: From these results, researchers assume that learning outcomes have increased. Because all students have exceeded the KKM limit set by the school, namely 70.